Assessing seawater intrusion and chloride zones in residents' wells in selected coastal area of Indonesia: A GIS analysis - Nurmaladewi, Nurmaladewi; Saktiansyah, La Ode Ahmad; Jayadisastra, Yoenita; Sulfitrana, Andini; Kaimuddin, Sitti Mikarna; Okto, Ali (Public Health of Indonesia, 2023)
Background: Seawater intrusion refers to the infiltration of seawater into groundwater, either naturally or artificially, due to the extraction of groundwater for domestic purposes. Seawater intrusion can have wide-ranging impacts on various aspects of life, including health issues, reduced soil fertility, structural damage, and groundwater contamination. In the Kendari District area, people rely on springs, dug wells, and drilled wells to fulfill their daily water needs, as well as for tourist and commercial activities. However, signs of seawater intrusion become evident when the water used by residents in the area becomes brackish or even saline. Objective: This study was to determine the distribution pattern of seawater intrusion and chloride zones in the coastal area of Kendari District, specifically within Kendari City, Indonesia. Methods: This study employed a descriptive research design and utilized purposive sampling to select the subjects. A total of 20 water samples were collected from residents in Kendari District, Kendari City. The research was conducted at various wells within the district. The collected data were then entered into a Geographic Information System (GIS) to analyze the distribution pattern of seawater intrusion and chloride zones in the coastal area of Kendari District, Kendari City. Results: The findings revealed an average pH of 7.11 (ranging from 5 to 8.8), an average temperature of 29.4°C (ranging from 29.4 to 32.7°C), an average Total Dissolved Solid (TDS) level of 590.25 mg/L (ranging from 54 to 1,388 mg/L), and an average salinity of 3.05‰ (ranging from 1 to 5‰). Conclusion: Based on these results, it can be concluded that seawater intrusion is classified as low and is not affecting the wells used by residents in the coastal area of Kendari District, Kendari City, Indonesia.